2024
DOI: 10.1186/s13741-024-00359-x
|View full text |Cite
|
Sign up to set email alerts
|

Multidisciplinary prehabilitation to improve frailty and functional capacity in high-risk elective surgical patients: a retrospective pilot study

Henry Man Kin Wong,
Ding Qi,
Bosco Hon Ming Ma
et al.

Abstract: Background Frailty is associated with worse outcomes and higher healthcare costs. The long waiting time for surgery is a potential ‘teachable’ moment. We examined the feasibility and safety of a pilot prehabilitation programme on high-risk frail patients undergoing major elective surgery. Methods A single-centre, retrospective pilot study (Dec 2020–Nov 2021) on a one-stop prehabilitation programme (structured exercise training, nutritional counsell… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…[17][18][19][20][21][22] Studies have suggested that while immediate postoperative outcomes, such as pain and anxiety, can be effectively managed through nursing interventions, [23][24][25][26][27] the long-term recovery of functional status may require a multidisciplinary approach that extends beyond the scope of nursing care alone. 28,29 This includes physical therapy and sustained patient education, emphasizing the complexity of postoperative recovery and the multifactorial nature of functional improvement status. 30 A major strength of our study lies in its comprehensive approach, and the use of meta-analysis to synthesize data from different sources.…”
Section: Discussionmentioning
confidence: 99%
“…[17][18][19][20][21][22] Studies have suggested that while immediate postoperative outcomes, such as pain and anxiety, can be effectively managed through nursing interventions, [23][24][25][26][27] the long-term recovery of functional status may require a multidisciplinary approach that extends beyond the scope of nursing care alone. 28,29 This includes physical therapy and sustained patient education, emphasizing the complexity of postoperative recovery and the multifactorial nature of functional improvement status. 30 A major strength of our study lies in its comprehensive approach, and the use of meta-analysis to synthesize data from different sources.…”
Section: Discussionmentioning
confidence: 99%